Uric Acid Biosensor Based on Biofilm of L. plantarum using Screen-Printed Carbon Electrode Modified by Magnetite - Dian Siska RF; Deden Saprudin; Dyah Iswantini; Novik Nurhidayat (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
Biosensor based on biofilm of L. plantarum has been successfully done for determination of uric acid in human urine compared with colorimetric enzymatic produced relative error of less than 5%. L. plantarum has uricase activity to react with uric acid, to maintain the stability of bacteria forming themselves into biofilms. Magnetite is known to increase sensitivity of the biosensor. The combination of magnetite-polyethylene glycol (Fe3O4-PEG) was used to modify the surface of Screen-Printed Carbon Electrode modified (SPCE) and the resulting modified electrode (biofilm/Fe3O4/PEG/SPCE) displayed good electrocatalytic activity to the oxidation of UA. The composition of biofilms with optical density 1, magnetite 100 mgmL-1 and PEG 3% v / v were able to increase the current up to 48% in 4mM of UA. The biosensor with an optimum composition produced good linearity with a concentration range, limit of detection, limit of quantitation, sensitivity, and repeatability were found to be 0.1 - 4.3 mM, 70 µM, 234 µM, 25.392 µA mM-1, 2.38%, respectively. This biosensor stable up to 49 days of measurement with the remaining activity was 90.70% and selective for interference compounds such as salt, urea, glucose, ascorbic acid. This method has a good stability, sensitivity, and potential application in clinical analysis.